Protection of fundamental rights in the light of freedom of information in Hungary - Péterfalvi, Attila (Revue internationale des Gouvernements Ouverts, 2017)
[extract] Information is the currency of democracy – This phrase is often attributed to US President Thomas Jefferson (although there is no evidence that Jefferson has ever used this phrase, rather, the quote first appeared in 1971 connected to Jefferson in a speech by US consumer advocate Ralph Nader.) Within the modern state administration concepts of good governance and fair administration the transparency of the public sphere is an essential element. The free flow of information is based on the right to freedom of information. Why is it important? Freedom of information (FOI) is not only a democratic demand but also an important tool against corruption. That’s why all the knowledge and practical impact of this constitutional right has to find its place in the legislation, public administration and education of the civil servants and other decision makers since they will be the responsible persons making decisions on whether to open or shut the door in front of the requests for the disclosure of public information. The protection of fundamental rights in the light of freedom of information in Hungary attracts great attention at international level nowadays.